2016
DOI: 10.1111/all.12800
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and dietary intake: an overview of systematic reviews

Abstract: Epidemiological research on the relationship between diet and asthma has increased in the last decade. Several components found in foods have been proposed to have a series of antioxidant, anti-allergic and anti-inflammatory properties, which can have a protective effect against asthma risk. Several literature reviews and critical appraisals have been published to summarize the existing evidence in this field. In the context of this EAACI Lifestyle and asthma Task Force, we summarize the evidence from existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
97
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 36 publications
3
97
1
4
Order By: Relevance
“…To our knowledge, only one longitudinal study on dietary patterns and asthma has been published and reported a small positive association between adherence to a Western diet and incident wheezing in children [23]. Regarding diet during adulthood, the few longitudinal studies show, overall, no association [11].…”
Section: Diet and Asthma: Primary Preventionmentioning
confidence: 93%
See 4 more Smart Citations
“…To our knowledge, only one longitudinal study on dietary patterns and asthma has been published and reported a small positive association between adherence to a Western diet and incident wheezing in children [23]. Regarding diet during adulthood, the few longitudinal studies show, overall, no association [11].…”
Section: Diet and Asthma: Primary Preventionmentioning
confidence: 93%
“…Regarding diet during childhood, few longitudinal studies have been published. The association between diet and childhood asthma is moderate, at best, with observational studies reporting 'protective' associations for fruits and vegetables, and fish intake [11,22]. To our knowledge, only one longitudinal study on dietary patterns and asthma has been published and reported a small positive association between adherence to a Western diet and incident wheezing in children [23].…”
Section: Diet and Asthma: Primary Preventionmentioning
confidence: 97%
See 3 more Smart Citations